Internet use, physical activity, and cognitive function in Chinese older adults: a cross-lagged panel analysis - Wang, Jinfu; Zhang, Na; Huang, Chengxin; Wu, Qinmei; Tong, Jin (Frontiers in Aging Neuroscience, 2025)
BackgroundWith the arrival of an aging society, cognitive health in older adults has become a global focal point. Cross-sectional studies have shown that internet use and physical activity may significantly affect cognitive function in older adults, but their longitudinal relationships and underlying mechanisms have not been fully explored.ObjectiveThis study aims to explore the relationship between internet use, physical activity, and cognitive function, and examine the mediating role of physical activity.MethodsThis study uses two rounds of longitudinal data from the China Health and Retirement Longitudinal Study (2018 and 2020), including a total of 2,383 individuals aged 60 and above. Cross-lagged regression analysis is used to test the bidirectional relationship between internet use and cognitive function, while a semi-longitudinal mediation model is used to examine the mediating role of physical activity.ResultsThe results indicate that there is a bidirectional relationship between internet use, physical activity levels, and cognitive function. Higher levels of internet use are associated with better cognitive function, and physical activity levels mediate the longitudinal relationship between internet use and cognitive function in older adults.ConclusionThis study reveals the complex relationship between cognitive function, internet use, and physical activity in older adults, and provides new perspectives for interventions aimed at improving cognitive health in older adults. Future research should further explore the dynamic changes between these variables to develop more effective intervention strategies and improve cognitive health and well-being in older adults.